Sharing@BookCafe_10 minutes spared to inculcate reading habits - Noorul Farina, Arifin (2019)
In the continuous efforts to inculcate reading habit among campus residents at University Malaysia Pahang (UMP), UMP Library recently held a “Jom Baca Bersama Untuk 10 Minit” programme under its Sharing@BookCafe (mailto:Sharing@BookCafe) activities.